The Effect of the Modified FIFA11+ Program on Special Endurance in Junior Soccer Players (Journal of Hama University, 2026)
Endurance is one of the most important components of physical fitness, and researchers have emphasized the need to develop and improve it due to its interconnectedness with other components of fitness. Researchers and specialists have emphasized the need to focus on developing this component, especially for juniors. Due to the sensitivity of this age group, researchers have focused on standardized and well-designed training programs that are appropriate for the target age group, including the FIFA11+ program.This study used the FIFA11+ program, approved by FIFA, where the researcher added a weight of 1 kg to each limb, based on the recommendations of the National Strength and Conditioning Association (NSCA) and the American Academy of Pediatrics (AAP), The aim of this research was to identify the effect of the modified FIFA11+ program on the level of change in endurance among young football players, compared to two warm-up programs (traditional and FIFA11+).The training program was implemented for (9) weeks on a sample of (24) players. The sample was divided into three equal groups (a control group and two experimental groups).After conducting the required tests and statistical processing, and presenting and discussing the results, the researcher concluded that the modified FIFA11+ program had an advantage over other warm-up programs in developing and improving endurance among young football players.The researcher attributed this advantage to the modification he made to the program, which was the addition of (1 kg) to each limb.Keywords: Football - Endurance - FIFA11+.